Investigation of the association between Rho/Rho-kinase gene polymorphisms and systemic sclerosis - Pehlivan, Yavuz; Yolbas, Servet; Cetin, Gozde Yildirim; Alibaz-Oner, Fatma; Cagatay, Yonca; Yilmaz, Neslihan; Onat, Ahmet Mesut (Springer Heidelberg, 2016)
Systemic sclerosis (SSc) is a disease characterized by inflammation, vascular abnormalities and fibrosis. The role of Rho/Rho-kinase pathway was demonstrated in the pathogenesis of fibrosis, inflammation and vascular abnormalities. This study was aimed to investigate the relation between SSc and Rho/Rho-kinase gene polymorphisms. The study included 339 patients with SSc and 302 healthy subjects who were apparently healthy and at similar age and gender. Genotype distributions and allele frequencies were detected by using Chi-square test or Fisher's exact Chi-square test between groups, and the haplotype analysis was applied using online program (SHEsis). Significant association was found in a polymorphism in the ROCK1 gene (rs35996865), a polymorphism in ROCK2 gene (rs10178332), a polymorphism in RhoA gene (rs2177268) and two polymorphisms in RhoC gene (rs11102522 and rs11538960) with SSc disease (p < 0.0022). In this study, association between SSc disease and Rho/Rho-kinase gene polymorphisms was investigated for the first time; significant associations between ROCK1, ROCK2, RhoA and RhoC gene polymorphisms and SSc disease were demonstrated. The results strongly suggest that this SNP may be an important risk factor for development of SSc. However, further validation of these findings in an independent cohort is necessary.
Keywords: Systemic sclerosis; Pathogenesis; Rho/Rho-kinase; Early diagnosis